2D material printer: a deterministic cross contamination-free transfer method for atomically layered materials. (22nd October 2018) - Hemnani, Rohit A; Tischler, Jason P; Carfano, Caitlin; Maiti, Rishi; Tahersima, Mohammad H; Bartels, Ludwig; Agarwal, Ritesh; Sorger, Volker J
Abstract: Precision and chip contamination-free placement of two-dimensional (2D) materials is expected to accelerate both the study of fundamental properties and novel device functionality. Current deterministic transfer methods of 2D materials onto an arbitrary substrate deploy viscoelastic stamping. However, these methods produce (a) significant cross-contamination of the substrate inherent from typical dense sources of 2D material flakes and (b) are challenged with respect to spatial alignment, and (c) multi-transfer at a single step. Here, we demonstrate a novel method of transferring 2D materials resembling the functionality known from printing; utilizing a combination of a sharp micro-stamper and viscoelastic polymer, we show precise placement of individual 2D materials resulting in vanishing cross-contamination to the substrate. Our 2D printer-method results in an aerial cross-contamination improvement of two to three orders of magnitude relative to state-of-the-art transfer methods from a source of average area for single flake ( 50 µ m 2 ). Moreover, we find that the 2D material quality is preserved in this transfer method. Testing this 2D material printer on taped-out integrated Silicon photonic chips, we find that the micro-stamper stamping transfer does not physically harm the underneath Silicon nanophotonic structures such as waveguides or micro-ring resonators receiving the 2D material. We further demonstrate functional devices such as Graphene tunnel junctions and transistors, and TMD-based material tunable microring resonators. Such accurate and substrate-benign transfer method for 2D materials could be industrialized for rapid device prototyping due to its high time-reduction, accuracy, and contamination-free process.